Design of circularly polarized and electrically small antenna with omnidirectional radiation pattern - Lertsakwimarn, Kittima; Phongcharoenpanich, Chuwong; Fukusako, Takeshi (My University, 2014)
This paper presents an electrically small and circularly polarized antenna with an omnidirectional radiation pattern. The antenna consists of a horizontal loop element enclosed by two U-shaped elements and a vertical element from the feeding point. The radiation pattern of the circular polarization is omnidirectional and has a maximum gain of -2 dBic in parallel to the ground plane at the 900 MHz band. The antenna dimensions are 48 × 20 × 13.8mm (0.14 λ × 0.06 λ × 0.04 λ) with ka = 0.476 (i.e. < 0.5), where k is the wavenumber at the resonant frequency and a is the radius of a sphere surrounding the antenna. The dimension corresponds to the definition of an electrically small antenna. The omnidirectional circularly polarized pattern of a prototype antenna shows good agreement with that of the simulation. In addition, this paper introduces a mechanism that generates omnidirectional circular polarization from electrically small antennas.
Keywords: Circular polarization; Electrically small antenna; Omnidirectional radiation pattern